Nursing and Health Care Preferences Among Opioid and Stimulant Using Black Sexual Minority Men: An Exploratory Study. (17th September 2021) - Dangerfield, Derek T.; Cooper, Jessica; Heidari, Omeid; Allen, Sophia; Winder, Terrell J.A.; Lucas, Gregory M.
Abstract: Black sexual minority men (BSMM) experience the worst HIV treatment outcomes in the United States. Drug use increases HIV transmission risks and reduces health care engagement. Perceived health care provider stigma and medical mistrust minimizes treatment efforts. This study identified nursing and health care preferences among drug-using BSMM. In-depth qualitative interviews were conducted among 30 BSMM who reported drug use in Baltimore City, MD, from December 2018 to March 2019. Analysis identified themes as client preferences for nursing practices and gaps in clinical services. Participants' ages ranged from 23 to 63 years ( M = 41.1). Most (91%) reported living with HIV. The following themes were identified as nursing and health care preferences: (a) being genuine, (b) knowing drug treatment and social services, (c) understanding drug use effects, (d) providing mental health services, and (e) clarifying treatment recommendations. Nurses and health care facilities can improve cultural competency for drug-using BSMM. Future research should identify the impact of these preferences on HIV care outcomes among BSMM.